TINGKAT PERTUMBUHAN TRUBUSAN ULIN (Eusideroxylon zwageri T. & B.) DALAM MENJAGA KELESTARIAN PADA IUPHHK PT. AYA YAYANG INDONESIA - Fadhlullah Fadhlullah; Mufidah Asy'ari; Wahyuni Ilham (Jurnal Sylva Scienteae, 2020)
Ulin (Eusideroxylon zwageri T. & B.), mostly known as the Belian or Iron Wood of Borneo. The spread of ulin can be found in Sumatra and Kalimantan. Nowaday, growth of Ulin is very threatened from extinction due to excessive exploitation by humans and its potential significantly decreased. As a result, natural growth and regeneration of Ulin becomes very slow and limited in its habitat. The sustainability of the results will be achieved if the harvested yields do not exceed the forest growth capability. It is necessary to measure and calculate growth of ulin sprout. This study aims to analyze the growth of ulin sprout in 2014 and 2018 periods. Based on field observation data were 31 samples of ulin sprout studied in May to November 2014 shows the result that none of the ulin sprout suffered dying. Subsequent observations in January 2018 found 29.04% ulin sprout or there are 9 dead of ulin sprout. The results showed that the average growth rate per month (CAI) Ulin sprout ranges from 0.197 cm per month, and at the stake level and 0.300 cm per month at the pole level. While the annual growth (MAI), at the level of stakes of 0.463 cm per year and at the pole level of 1,147 cm per year.Keywords: Ulin sprout; Growth rate